1976
DOI: 10.1002/jbm.820100207
|View full text |Cite
|
Sign up to set email alerts
|

Tendon grafting with glutaraldehyde fixed material

Abstract: An evaluation of 0.2% buffered glutaraldehyde fixed tendon as a potential tendon replacement prosthesis was evaluated in rabbit and chicken models. In vivo implantations were done to determine compatability, function, and strength of grafts. Autogenous fresh grafts were used as controls in the strength evaluations. The fixed tendon elicits no cellular rejection response, is invaded and replaced by host tissues, and anastomosis strength in tension compares favorably to a fresh autogenous control. These prelimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…GA cross-linked bioprostheses are not generally finally sterilized as the processing solutions are bacteriocidal (12). Some implants are stored in GA or formaldehyde to maintain sterility (10,12,23). Final sterilization was deemed necessary in this study as only those tendons prepared in the higher concentrations of GA were exposed to bacteriocidal concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…GA cross-linked bioprostheses are not generally finally sterilized as the processing solutions are bacteriocidal (12). Some implants are stored in GA or formaldehyde to maintain sterility (10,12,23). Final sterilization was deemed necessary in this study as only those tendons prepared in the higher concentrations of GA were exposed to bacteriocidal concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting polypyrrole-coated substrates were rinsed with deionized water and air-dried. Following substrate preparation, a linker, glutaraldehyde, was covalently attached by treating the polypyrrole-coated substrates with 25% glutaraldehyde for 4 h, facilitating flexible bridges for effective binding of biomolecules [ 63 , 64 ]. After washing with phosphate-buffered saline (PBS), site-specific SARS-CoV-2 RBD lactam-stapled hACE-2 peptide was covalently immobilized onto the glutaraldehyde-treated substrates at 30 µg/mL concentration in 1× PBS for 16 h. Excess and unbound peptide were removed by washing with 1× Tris-buffered saline with Tween20 (TBST).…”
Section: Methodsmentioning
confidence: 99%
“…One study demonstrated the strength of stabilized collagen as well as its resistance to collagenase attack (18). Evaluation of glutaraldehydefixed tendon materials demonstrated biologic acceptability when implanted subcutaneously or as tendon grafts (17,20). Glutaraldehyde-stabilized material was shown to function suitably as a prosthesis in an evaluation of the replacement of the medial collateral ligament in a rabbit model (19).…”
mentioning
confidence: 99%